2007
DOI: 10.7205/milmed.172.4.426
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Analysis of Hearing Loss among Navy Personnel

Abstract: Hearing loss is one of the most common disabilities among sailors. Service members are posted to a variety of stations. Many of these posts have high noise levels, and particular ratings have high exposure. If assignments of higher risk can be identified, then focused prevention programs can be implemented. The focus of this study was to determine how hearing loss relates to service time spent aboard ships. To investigate which duty stations and ratings are at high risk for hearing loss, this study looked at m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0
9

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 7 publications
2
13
0
9
Order By: Relevance
“…This prevalence was close to the results found for US Navy officers (38.0%), 11 and slightly lower than those for workers in fishing boats (50.5%). 22 Thus, hearing loss seems to be one of the common disabilities among Thai naval officers.…”
Section: Discussionsupporting
confidence: 87%
“…This prevalence was close to the results found for US Navy officers (38.0%), 11 and slightly lower than those for workers in fishing boats (50.5%). 22 Thus, hearing loss seems to be one of the common disabilities among Thai naval officers.…”
Section: Discussionsupporting
confidence: 87%
“…In the military, NIHL may negatively affect a soldier's performance in combat and imposes a large financial burden in disability payments (McIlwain et al, 2008;Trost and Shaw, 2007). In some cases, NIHL may be preventable by avoidance of high noise levels and by using hearing protective devices.…”
Section: Introductionmentioning
confidence: 99%
“…[3] reported that nearly one-half million U.S. Veterans are service-connected (i.e., receive disability compensation) for hearing loss, that hearing loss leads to higher attrition rates than for those without hearing loss, and that those deployed with combat experience had a 1.6% greater chance of reporting new hearing loss compared to those not deployed. Trost and Shaw[4] analyzed medical hearing test records for nearly 268,000 enlisted Sailors, and found that personnel who had been deployed 2/3 rd time to surface warships had an 18 percentage-point higher chance of leaving active duty with hearing loss compared to those limited to shore duty, and those deployed to sea duty ½ time had a 13 percentage point probability increase. In summary, these results indicate that exposure to loud ongoing and impulse noises in military settings can impact workplace safety and effectiveness, auditory fitness for duty, and risk of NIHL and tinnitus.…”
Section: Introductionmentioning
confidence: 99%